Influence of groove wheel discharger on the discharge pulsation characteristics of agricultural materials - Ru, Yu; Xia, Daming; Rong, Zifan; Zhang, Xiao (International Journal of Agricultural and Biological Engineering, 2025)
The external groove wheel discharger has good versatility and can adapt well to materials of different particle sizes (seeds or fertilizers). However, the flow pulsation phenomenon during the working process may lead to a decrease in the efficiency of the operation, and thus optimization is needed. In this study, the straight-tooth groove wheel discharger was taken as the research object, and a discrete element model of the discharger in operation was established. The coefficient of variation of the flow pulsation was used as the evaluation index; the effective length of the groove wheel, the groove speed of the groove wheel, the arc length of the inverted tongue chamfer, and the radius of the concave groove were taken as the experimental factors; and a four-factor and five-level orthogonal regression rotation combination simulation experiment was conducted. A mathematical regression model of the coefficient of variation of the discharge pulsation was established to optimize each factor. The results showed that when the effective length of the groove wheel was 45 mm, the groove speed was 54 r/min, the arc length of the discharge tongue chamfer was 19 mm, and the groove radius was 12 mm, the coefficient of variation of the flow pulsation was optimal. The simulation results were consistent with the model predictions. Under the optimized parameters, simulation experiments on the flow pulsation of urea (spherical shape) and rice (ellipsoidal shape) particles were carried out separately. The results showed that under the same structure and working parameters, there were significant differences in the coefficient of variation of the flow pulsation between the two types of particles, with the rice particles having a larger overall coefficient of variation. Within the optimization constraint range of the groove speed, the coefficient of variation of the flow pulsation of rice particles gradually decreased and tended to be stable with the increase of the groove speed, while that of urea particles decreased first and then increased with the increase of the groove speed. After increasing the groove radius, the coefficient of variation of the flow pulsation of rice particles decreased overall, and the pulsation was improved, which was consistent with the results of the platform verification and simulation. Therefore, when using the external groove wheel discharger for different types of agricultural materials, the groove wheel can be replaced according to the different materials to meet the requirement of uniform discharge, which is conducive to the development of precision agriculture and of great significance. Keywords: groove wheel, agricultural materials, discrete element method (DEM), response surface, optimal design DOI: 10.25165/j.ijabe.20251801.8431 Citation: Ru Y, Xia D M, Rong Z F, Zhang X. Influence of groove wheel discharger on the discharge pulsation characteristics of agricultural materials. Int J Agric & Biol Eng, 2025; 18(1): 83–91.